Developing a basis for heavy metal in-situ detection using CZT. (1st May 2022) - Foley, A.; Mohanty, S.K.; Sjoden, G.E.
Abstract: Heavy metal contamination is a global concern–this type of contamination in the environment has been on the rise since the industrial age. Current guidelines from the United States Environmental Protection Agency and the World Health Organization limit arsenic concentration in water sources to 10 μg/kg. Typically, detection of heavy metals in industrial processes include spectrophotometry and colorimetry. A viable alternative for heavy metal detection can be implemented using a room temperature gamma spectrometer paired with a portable neutron generator for in-situ neutron activation analysis. In this paper, we explore detection of an arsenic salt diluted in a water sample to specific concentrations; the arsenic sample is utilized to determine the capability of a 5 mm × 5 mm × 5 mm CZT detector for heavy metal detection by neutron activation analysis. Several arsenic dilutions were irradiated in the University of Utah TRIGA reactor (UUTR), and the samples were measured on both HPGe and CZT detectors. The direct comparator method was used to determine the sample mass in a sample attributed by each detector, and the results were compared to the known dilution arsenic mass. We determined that a CZT gamma spectrometer can reliably detect 10 mg/kg arsenic with high confidence, and as low as 1 mg/kg arsenic with low confidence. For comparison, an HPGe gamma spectrometer can reliably detect 1 mg/kg arsenic with high confidence, and as low as 0.1 mg/kg with low confidence. Based upon our MDA, the CZT spectrometer can detect samples with a total activity of 1.8×10 -5 mCi and higher, and the HPGe detector can detect an activity of 1.8×10 -6 mCi. These results suggest the method has potential in portable gamma spectrometry solutions for wastewater effluents from industrial processes such as paint manufacturing, pharmaceutical, and smelting operations.